Effect of iron deficiency anemia on lipid peroxidation and antioxidant systems - Madhikarmi, NL; Murthy, KRS (Journal of College of Medical Sciences-Nepal, 2012)
Iron deficiency is one of the most widespread nutritional deficiencies in the world. Globally more than two billion people are suffering from iron deficiency anemia. The present study was designed to investigate the influence of a large number of factors known to be associated with oxidative stress. The case-control study determines the lipid peroxidation and antioxidants status in forty Iron deficiency anemia and forty healthy volunteers with their informed consent. All the parameters were assayed by spectrophotometric methods. Blood hemoglobin and plasma iron were decreased whereas total iron binding capacity was increased significantly in Iron deficiency anemia. The lipid peroxidation parameters like malondialdehyde, lipid hydroperoxide were significantly increased in Iron deficiency anemia. Both enzymatic; glutathione peroxidase, superoxide dismutase and catalase and non-enzymatic antioxidants; vitamin C, E and reduced glutathione were significantly decreased in Iron deficiency anemia case as compared to their healthy counterparts. Our findings suggest, increased lipid peroxidation products and reduced antioxidants system boost the oxidative stress state, hence deteriorating the condition of Iron deficiency anemia patients. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 34-43 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6739